Data for: Evaluating Maize Shelling Technologies for Mexican Smallholders: Performance, Quality, and Decision Framework for Optimal Selection - Van Loon, Jelle; López-Gómez, Jesús; Odjo, Sylvanus (International Maize and Wheat Improvement Center, 2024)
CIMMYT implemented a study at its station in Texcoco, Mexico to compare the effectiveness of 7 different commercially available shelling options for smallholder farmers in Mexico (OCT: hand sheller; DSG: manual crank-type sheller; THDG: pedal sheller; DEZ: electric sheller of Chinese make; RDI: electric rotating-disc sheller; MKT: two-wheel tractor, diesel-engine-powered sheller from Mexico (Mekatech brand); HER: stand-alone, petrol-engine-powered sheller from Mexico (Herconth brand)). The data collected before and after the shelling experiments included: (1) characteristics of the maize varieties evaluated; (2) description of the evaluated shellers; (3) working efficiency of the evaluated shellers; (4) grain and seed quality parameters of the maize varieties.